An analysis of motivation perspectives in small construction companies - Hans PRESULLI (Communications of International Proceedings, 2023)
Studies that are circulated in the media these days usually only reflect statistical key figures at a highly aggregated level, where, however, small businesses are usually underrepresented in their individuality among the averaged values. The motivation for this study arose from the study of literature in the course of a dissertation, where it became apparent that high-quality research deals with various aspects of small business but does not explore the dynamic occurrence of this performance of the company's employees, who are usually led in groups. State or institutionally conducted studies usually focus on macroeconomic effects that are intended to serve as a trend analysis, but rarely on microeconomic processes because, according to the prevailing opinion, they are reflected in business ratios. This one-dimensional view can lead to a desensitization of interdisciplinary as well as socio-cultural contexts as well as to economic "drifts". To address this research gap, the need to conduct this preliminary study became vacant. From a methodological point of view, interviews were held with key people during and after the work was carried out, and subtle and difficult-to-differentiate factors were connoted through careful observation during the field research and converted into an overall metric through suitable triangulation. The preliminary study, held in small cohorts, shed light on the performance of the trade execution in the context of a naturally developed group leadership style. The performance was measured across different trades, the average duration of which, together with the quality of execution, was determined empirically in advance. The cross-sectional data generated from this were transformed into an adequate Likert scale and transferred to an equally weighted, arithmetically averaged overall assessment, after which the dissociated analysis began. If necessary, the analysis of the influence of the group leadership style on the overall performance was supplemented by the author's empirical values to finally present the research results categorically and conclude them to be able to discuss.
Keywords: Motivations; Willpower; Training